Opportunity and Incremental Cost: An Attempt to Define in Systems Terms. - McRae, T. W. (The Accounting Review, 1970)
Abstract The various aspects of cost provide the conceptual core of management accounting. Incremental cost and opportunity cost are particularly important concepts, since they provide the foundations for the accountant's contribution to decision-making. The article sets out to test the validity of the two concepts. It says that there seem to be some confusion as to the precise meaning of the terms incremental and opportunity cost. The confusion exists in the literature of management accounting, managerial economics, and pure economics. The article suggests that a definition, using systems terminology, can help to clarify the meaning of the two terms. It defines incremental cost as the sum of the opportunity costs of the inputs to a system, each input being used independently of other inputs. Opportunity cost is defined as the revenue sacrificed by not implementing the next best alternative output from the resources making up a system. It is seen that incremental cost provides a floor to opportunity cost. The task of measuring opportunity cost is synonymous with the task of maximizing the profit from the use of the resources under a firm's control. The accountant cannot be expected to tackle this problem alone.